Higher dietary magnesium and potassium intake are associated with lower body fat in people with impaired glucose tolerance - Chu, Natural; Chan, Tsz Yeung; Chu, Yuen Kiu; Ling, James; He, Jie; Leung, Kathy; Ma, Ronald C. W.; Chan, Juliana C. N.; Chow, Elaine (Frontiers in Nutrition, 2023)
Introduction: Obesity and diabetes are public health concerns worldwide, but few studies have examined the habitual intake of minerals on body composition in people with prediabetes. Methods: In this prospective cross-sectional study, 155 Chinese subjects with IGT (median age: 59(53-62) years, 58% female) had an assessment of body composition including body fat percentage, oral glucose tolerance tests (OGTT), Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) and 3-day food records from nutritional programme analysis. Results: Dietary intake of minerals was negatively correlated with body fat. People with obesity had the lowest daily consumption of iron median (IQR) 10.3 (6.9-13.3) mg, magnesium 224 (181-282) mg, and potassium 1973 (1563-2357) mg when compared to overweight (10.5 (8.0-14.5) mg, 273 (221-335) mg, and 2204 (1720-2650) mg) and normal weight individuals (13.2 (10.0-18.6) mg, 313 (243-368) mg, and 2295 (1833-3037) mg) (p = 0.008, < 0.0001 and 0.013 respectively). Amongst targeted minerals, higher dietary magnesium and potassium intake remained significantly associated with lower body fat after the adjustment of age, gender, macronutrients, fiber, and physical activity. Conclusion: Dietary magnesium and potassium intake may be associated with lower body fat in people with impaired glucose tolerance. Inadequate dietary mineral intake may play contribute to obesity and metabolic disorders independent of macronutrients and fiber consumption.